Performance of Composite Portland Cements with Calcined Illite Clay and Limestone Filler Produced by Industrial Intergrinding - Irassar, Edgardo Fabián (2023)
The performance of five composite Portland cements (CPCs) with limestone filler (LF = 10%–25% by mass) and calcined illite clay (CIC = 10%–25% by mass) elaborated by intergrinding was analyzed in paste, mortar, and concrete. Hydration was studied by isothermal calorimetry, bound water, and XRD. Flow and compressive strength (2 to 90 days) were determined in standard mortar. Concretes (w/b = 0.45; binder content = 350 kg/m3; slump = 15 ± 3 cm) were elaborated to determine compressive and flexural strength, water penetration, and chloride migration. Intergrinding CPCs have a large specific surface area when LF + CIC increases, with a similar size range of clinker particles. Supplementary cementing material replacements decreased the heat rate, prolonged the dormant period, and decreased the acceleration rate at early ages. According to the Fratini test, all CPCs had positive pozzolanicity after 28 days, but XRD analysis showed Ca(OH)2 associated with monocarboaluminate phases. Mortar flow was slightly reduced when the proportion of CIC was increased. Mortar strength decreased when the sum of LF + CIC increased. CPC strength class was limited by compressive strength after 28 days. Concretes were workable, and the compressive strength after 28 days depended on the LF + CIC, and CIC contributed after 90 days. After 28 days, the water penetration depended mainly on the LF + CIC content. The chloride migration coefficient was also reduced when CPC contained more CIC and less LF.